Об устойчивости и ограниченности движений относительно части переменных в метрическом пространстве - Мартынюк, А.А.; Денисенко, В.С. (Видавничий дім "Академперіодика" НАН України, 2008)
We present an results a new Lyapunov stability with respect to a part of variables for dynamical systems in a metric space. This model is very general and includes most of the nonlinear systems considered in the literature as special cases. We apply the matrix-valued mapping preserving the stability and the comparison principle.